Interaktywna ekspozycja wartości: światopoglądowe manifestacje polskich intelektualistów w dobie wirtualizacji komunikacji - Peciakowski, Tomasz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2021)
The article attempts to establish in what way values manifest themselves in the virtual communication undertaken by Polish intellectuals – creators of culture involved in public life. The article uses qualitative content analysis as its research method. The analysis focuses, firstly, on identifying thematic threads present in posts published by the researched authors; secondly, on distinguishing those threads that relate to axiology; and thirdly, on the discursive analysis of the selected material, in order to explore deeply their content for its axiological message. When on social media, intellectuals use tools of engaged and engaging communication – emotional, axiologically marked, often controversial. The article discusses four forms of communication built this way: recommendation, idea placement, externalization and protest.